THE RELATIONSHIP OF LONG INSTALLATION REGARDING THE PRESENCE OF CATHETER LEVEL OF ANXIETY INPATIENTS AT PMI HOSPITAL BOGOR: HUBUNGAN LAMA PEMASANGAN KATETER DENGAN TINGKAT KECEMASAN PADA PASIEN RAWAT INAP DI RS PMI KOTA BOGOR - Sara Sara Tania (Jurnal Ilmiah Wijaya, 2019)
The number of disorders, anxiety reached 5% of the world’s population. The comparison with anxiety disorders in women and men is 2 to 1. It is estimated that 2%-4% of the world have experienced anxiety disorders. Anxiety to be caused by disease, the cost of treatment, a new environment, diagnostic procedures, treatment and procedures of nursing, including acts of invasive like surgery, the act of taking blood, the installation of a catheter and others. To determine the relationship long the installation of a catheter with the level of anxiety in patients hospitalized in PMI Hospital of Bogor City. This kind of research is analytic with cross sectional desain. The method of taking samples in this study with a Quota Sampling technique with sample of 68 respondents. Collection of data obtainbed through teh distribution of a questinnare and observation. Based on the results of the research that 22 respondents (44,0%) be categorized not long to having too low. The Statistical test result were obtained by using chi square that p value = 0,023, which means p value < 0,05 then Ho is reject and Ha accepted. So that, there is relationship between the installation of a catheter with level anxiety inpatients PMI Hospital Bogor. The researcher expected that this research can provide information to the hospital in the framework of the quality of nursing services, especially in touch with a patient attached the catheter to experience anxiety.